Revealing the Side‐Chain‐Dependent Ordering Transition of Highly Crystalline Double‐Cable Conjugated Polymers. (22nd October 2021) - Feng, Guitao; Tan, Wenliang; Karuthedath, Safakath; Li, Cheng; Jiao, Xuechen; Liu, Amelia C. Y.; Venugopal, Hariprasad; Tang, Zheng; Ye, Long; Laquai, Frédéric; McNeill, Christopher R.; Li, Weiwei
Abstract: We developed a series of highly crystalline double‐cable conjugated polymers for application in single‐component organic solar cells (SCOSCs). These polymers contain conjugated backbones as electron donor and pendant perylene bisimide units (PBIs) as electron acceptor. PBIs are connected to the backbone via alkyl units varying from hexyl (C6 H12 ) to eicosyl (C20 H40 ) as flexible linkers. For double‐cable polymers with short linkers, the PBIs tend to stack in a head‐to‐head fashion, resulting in large d ‐spacings (e.g. 64 Å for the polymer P12 with C12 H24 linker) along the lamellar stacking direction. When the length of the linker groups is longer than a certain length, the PBIs instead adopt a more ordered packing likely via H ‐aggregation, resulting in short d ‐spacings (e.g. 50 Å for the polymer P16 with C16 H32 linker). This work highlights the importance of linker length on the molecular packing of the acceptor units and the influences on the photovoltaic performance of SCOSCs. Abstract : When switching the alkyl linkers from C12 H24 to C16 H32 in double‐cable conjugated polymers, perylene bisimide side units exhibited order phase transition from disordered structures to ordered H ‐aggregation, which is strongly correlated to the photovoltaic performance in single‐component organic solar cells.